Exploring Soil Biota and Chemical Dynamics in Palm Oil Cultivation: Insights from Cikabayan, Bogor - Adiyaksa, Ivan Khofian; Widyastuti, Rahayu; Putri Wulandari, Dwi; A M Zuhud, Ervizal (Media Konservasi, 2024)
Soil biological properties sometimes escape attention from environmental studies, especially regarding land use change. Several studies on diversity have been conducted in palm oil. However, most of the studies only focus on certain genera or order and have not yet depicted the micro-ecosystem in the soil. This study aims to analyze the interaction between soil biological properties and soil chemical properties through a correlation study using Randomized Block Design (RBD) to simplify the system in the micro-ecosystem. The result showed that most soil microbe parameters have complex and different interactions with soil chemical properties. Soil biological properties, such as the total microbes (TM) and Azotobacter (Az), significantly correlated toward phosphate and potassium, respectively. Furthermore, mesofauna and macrofauna have a negative and weak correlation with pH and a negative and moderate correlation towards Phosphate (P) content in the soil. This negative and moderate correlation strength happened due to increased soil acidity, leading to a higher chance of H2PO4- interacting with metal ions, resulting in a high risk of toxicity. Soil chemical properties have complex interactions with soil biological properties, and each will affect the others to balance the chemical cycling in the soil. Thus, this study showed the importance of preserving the natural balance of cultivated areas, in this case, palm oil plantations, so that the well-preserved ecosystem will give its benefits.